THE EFFECT OH THE COMBINATION TOFU AND BRAN FERMENTATION ON THE GROWTH OH THE POPULATION Daphnia sp - Zakiyah, Fuji; Diniarti, Nanda; Dwi Hari Setyono, Bagus (Jurnal Perikanan Unram, 2019)
Daphnia magna is an animal Crustacea which is often referred to as small-sized water lice that live in freshwater and is one of the natural feeds for aquatic larvae which are easily digested, their size is in accordance with mouth openings, has high nutrient content, contains essential amino acids which high and can be cultivated in bulk. Tofu pulp and bran organic fermented with probiotic bacteria are expected to increase the efficiency of feed utilization and growth of Daphnia magna. This study aims to determine the effect of the combination of tofu and bran fermentation results on the population and determine the best combination of feed with tofu pulp and bran fermentation which results in high growth of Daphnia magna. This study used a Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications to obtain 12 experimental units. Treatment A: control (commercial feeding), treatment B (giving 0.15 g / l tofu dregs and 0.3 gl bran), treatment C (giving 0.3 g / l tofu dregs), and treatment D (giving 0 , 6 g / l bran). The results of this study indicate that the administration of tofu pulp and bran through the probiotic fermentation process affects population density, population growth rate, and biomass production of Daphnia magna. Treatment B is the best treatment with the highest population density of 246.67 ind / l, population growth rate of 5.199% / day, and biomass production of 340 mg / l.